Busca de inibidores da catepsina K em plantas medicinais utilizadas no tratamento de doenças osteoarticulares - Silva, James Almada da (2011)
Ten herbs used in traditional medicine supported by literature for its effectiveness to osteoarticular diseases were selected to conduct a screening of inhibition activity against the cathepsin K, an important enzyme responsible for cleavage of collagen, the main constituent of extracellular matrix of cartilage and bone. Out of the ten herbs selected (ginger, saffron, camellia, cat s claw, mentrasto , moringa , babaçu , devil s claw, urtica e pequi ), one, gengibre (Z. officinale), should be highlighted by a high inhibitory activity of its extracts and fractions against cathepsin K and due to its ancient use as a therapeutic agent. From the dichloromethane fraction obtained of the crude extract of the rhizome of Z. officinale were isolated and identified 18 compounds (4-gingerol, 6-gingerol, 8-gingerol, 6-shogaol, 8-shogaol, 10-shogaol, 6- paradol, 6-gingerdiol, methyl 6-gingerol, methyl 6-shogaol, diacetoxy-6-gingerdiol, methyl diacetoxy-6-gingerdiol, zingerone, gingerenone A, galanolactone, 3-acetoxy- 5-hydroxy-1,7-bis(4 -hydroxy-3 -methoxyphenyl)-heptane and hexahydrocurcumin). From the hexane fraction and essential oil were identified two monoterpenes and four sesquiterpenes. The most active compounds against cathepsin K were gingerols and shogaols with longer alkyl chain. Optimization of the separation of major compounds (6, 8 and 10-gingerol) and an overload study of C18 column was performed using HPLC, obtained as result dozens to hundreds of milligrams of each gingerol with high purity. Structural modifications of 6-gingerol were carried out and of the seven derivatives obtained 4 presented significant increase in inhibition of cathepsin K. Of all the compounds, three, SSi6, 10-gingerol, 6-shogaol, were selected for later tests: determinating of the mode the inhibition against cathepsin K, inhibition against cathepsin K and inhibition of nitric oxide (NO) production, in cellular culture. The inhibitions determined were: partially noncompetitive, partially uncompetitive and complete uncompetitive for the SSi6, 10-gingerol and 6-shogaol, respectively. Excellent inhibition activity against the cathepsin K, in cellular culture, can be observed for SSi6 and 6-shogaol. In the inhibition assay of NO production, the 6- shogaol was the only compound that appeared as effective.